Air Pollution: What are perspectives of Greek students? - Μarinou, M.; Argyri, P. (Open Schools Journal for Open Science, 2020)
In this paper, we analyze the causes and effects of the phenomenon of Air pollution. based on research evidence on a global scale. Our aim is to inform people about this burning issue and to propose solutions to the problem. Thus, we have asked for an impact on students’ community through questionnaires. The results for the resolution include our inclusiveness in the problem and our efforts to make a collaborative environment with stakeholders.